Dome-shaped mode lasing from liquid crystals for full-color lasers and high-sensitivity detection - Duan, Rui (2023)
In this communication, we report a new class of oscillation mode, dome-shaped mode (DSM), in liquid crystal (LC) microlasers. A record high Q-factor over 24 000 is achieved in LC soft-matter microlasers. We successfully presented a proof-of-concept demonstration of red, green, blue (RGB) LC-DSM microlaser pixels with a 74% broader achievable color gamut than the standard RGB color space. Besides, the detection limit for acetone vapor molecules is as low as 0.5 ppm, confirming the excellent potential of the proposed LC-DSM microlaser in ultra-high sensitivity detection.